2020
DOI: 10.2147/ijgm.s241320
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combined Effect of Coffee Consumption and Cigarette Smoking on Serum Levels of Vitamin B12, Folic Acid, and Lipid Profile in Young Male: A Cross-Sectional Study [Corrigendum]</p>

Abstract: Upon reviewing the published article, the authors noticed an error that they had overlooked while completing their revisions. The affiliation of Beisan A Mohammad is incorrect. On page 421 the current author details read:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“… CCR: coffee consumption rate TG: HCR: heavy coffee consumption rate; MCR: moderate coffee consumption rate; NCR: no coffee consumption rate; TG: triglycerides; TC: total cholesterol; HDL: high-density lipoprotein; DV: dependent variable; IV: independent variable; R: Pearson correlation coefficient; R 2 : regression; F: variation between sample means/variation within the samples; n: number of participants; SVD: severe vitamin D deficiency; DVD: deficiency of vitamin D; IVD: insufficiency of vitamin D. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… CCR: coffee consumption rate TG: HCR: heavy coffee consumption rate; MCR: moderate coffee consumption rate; NCR: no coffee consumption rate; TG: triglycerides; TC: total cholesterol; HDL: high-density lipoprotein; DV: dependent variable; IV: independent variable; R: Pearson correlation coefficient; R 2 : regression; F: variation between sample means/variation within the samples; n: number of participants; SVD: severe vitamin D deficiency; DVD: deficiency of vitamin D; IVD: insufficiency of vitamin D. …”
Section: Resultsmentioning
confidence: 99%
“…Each participant was contacted by telephone and asked to complete a questionnaire that included questions about her anthropometric and clinical features as well as her coffee consumption in the 3 months before study admission, as described in the previous related study. 2 Following completion of the questionnaire, the participants were required to provide blood samples for analysis at Ibn Al-Haytham Hospital Laboratory in Amman, Jordan, to measure 25OHD levels.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Though, the levels of TC and LDL-C in hyperlipidemic adults have been correlated with the distinct influence of hepatocellular carcinoma (HCC), certain plasma protein markers, and cigarette smoking in animal and humans model. However, several studies revealed that caffeine levels have a major influence or no influence on the lipid profile parameters (Ashakumary and Vijayammal 1997;Vlachopoulos et al 2004;Nystad et al 2010;Al Hariri et al 2016;Abu-Taha et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This prompted the design of this study to evaluate the diverse effects of the high consumption rate of medium roasted coffee. The attention was drawn to the importance of verification to clarify whether higher intakes of roasted coffee (compared to the moderate consumption rate, 1-2 cups/day) influence the non-HDL level as a predictor of CVD risk (Abu-Taha et al 2020). The significant positive correlation observed between coffee consumption and lipid profile parameters did not include HDL-C, which was consistent with a previous study (Cai et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation